FENOMENA PERNIKAHAN DINI DI INDONESIA : PERSPEKTIF HUKUM KELUARGA ISLAM - umah, Habibah Nurul Umah (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2020)
Child marriage is a social phenomenon that commonly happens in all places. This sort of marriage is like iceberg phenomenon which emerges a little bit in the surface, it is rarely exposed, but it is commonly practiced in wider community. Child marriage has become one of the most controversial issues in Islamic family law. Some scholars approve the practice without any reservations while other do not. The substance of the Islamic law is create a better life for society now and in the future. If it is found that child marriage in contemporary societies has resulted in many negative effects then it should be legally disapproved.